2018
DOI: 10.1097/mao.0000000000001861
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History and Rehabilitative Outcomes of Hearing Loss in Congenital Cytomegalovirus: A Systematic Review

Abstract: Late onset and progressive hearing loss is seen in children who develop hearing loss from cCMV. Frequent audiologic follow-up is necessary considering the natural history of cCMV hearing loss. Universal screening should be pursued due to the number of asymptomatic children, at birth, who develop late onset/delayed hearing loss. CI is an effective means of improving speech and language in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 57 publications
7
25
0
Order By: Relevance
“…All cCMV neonates have so far shown no neurological sequela in the present study. However, some proportion of children develop SNHL despite showing asymptomatic cCMV at birth [2729]. Although antiviral therapy may prevent development of SNHL for such children with cCMV, evidence for the efficacy of this treatment remains lacking [30].…”
Section: Discussionmentioning
confidence: 99%
“…All cCMV neonates have so far shown no neurological sequela in the present study. However, some proportion of children develop SNHL despite showing asymptomatic cCMV at birth [2729]. Although antiviral therapy may prevent development of SNHL for such children with cCMV, evidence for the efficacy of this treatment remains lacking [30].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the international guidelines recommend follow-up until the age of six. [5,23,24] . As for the neurodevelopmental follow-up, this is a good timing.…”
Section: ]mentioning
confidence: 99%
“…Even if a child with cCMV is born with normal hearing, a progressive SNHL can occur later in life and have adverse effects on speech development. For example, Fletcher et al ( 15 ) found a wide variance (9–68%) in onset time of SNHL based on information from 36 previous studies. In a retrospective case study by Kim et al ( 16 ), 11 out of 58 children (19%) with cCMV had SNHL, but the majority of them were not identified as having hearing loss (HL) during the hospital hearing screening, suggesting SNHL can occur later in life for this population even after passing a newborn hearing screening.…”
Section: Discussionmentioning
confidence: 99%